Lyapunov-based anomaly detection in preferential attachment networks - Ruiz, Diego; Finke, Jorge (Zielona Góra: Uniwersytet Zielonogórski)
Network models aim to explain patterns of empirical relationships based on mechanisms that operate under various principles for establishing and removing links. The principle of preferential attachment forms a basis for the well-known Barabási - Albert model, which describes a stochastic preferential attachment process where newly added nodes tend to connect to the more highly connected ones. Previous work has shown that a wide class of such models are able to recreate power law degree distributions.
Keywords: network formation models; discrete event systems; stability; anomalous event detection